∫(sinx+cosx)^2 dx ∫(sinx+cosx)^2 dx
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 19:45:29
∫(sinx+cosx)^2dx∫(sinx+cosx)^2dx∫(sinx+cosx)^2dx∫(sinx+cosx)^2dx∫(sinx+cosx)^2dx∫(sinx+cosx)^2dx原式=∫
∫(sinx+cosx)^2 dx ∫(sinx+cosx)^2 dx
∫(sinx+cosx)^2 dx
∫(sinx+cosx)^2 dx
∫(sinx+cosx)^2 dx ∫(sinx+cosx)^2 dx
原式=∫(sin²x+cos²x+2sinxcosx)dx
=∫(1+sin2x)dx
=1/2∫(1+sin2x)d2x
=x-cos2x+C
∫(sinx+cosx)^2 dx ∫(sinx+cosx)^2 dx
∫(cosx)^2/(cosx-sinx)dx
∫cosx/sinx(1+sinx)^2dx
∫dx/(sinx+cosx)
∫(sinx-cosx)dx
∫cosx / (cosx+sinx)dx
∫sinx/(sinx-cosx)dx
∫sinx/(cosx-sinx )dx
∫(2sinx+cosx)/(sinx+2cosx)dx
一道积分题,∫[(cosx-sinx)/(cosx+2sinx)]dx
求怎么解这题?! ∫ (cosx + 2sinx)/(sinx - cosx) dx
∫cosx/【2+(sinx)^2】dx=?
∫1/sinx^2cosx^2 dx
∫(sinx)^2/(cosx)^3 dx
∫x^2 sinx cosx dx ..
∫(cosx^2/sinx^3)dx
∫(sinx)^3/(2+cosx)dx
∫(x^2)(cosx^3)(sinx)dx